Impact of Problem-Based Learning Models with a Contextual Approach on the Learning Competence of Students in Junior High School - Khairil Arif; Olyivia Retdwina Rusma; Helmia Niati Efna; Dyah Nawang Sari; Silvi Jafreli (Postgraduate, University of Mataram, 2024)
The education of the natural sciences is closely linked to environmental issues. One of the most accurate models used is the problem-learning model. This study aims to look at the impact of a problem-based learning model. With a contextual approach to the competence of high school students, this research is an experimental study using a non-equivalent group design. Based on statistical analysis of the cognitive, psychomotor, and affective aspects of the students, it is known that the data is distributed normally but homogeneously. Then the hypothesis was tested using an independent t test, with the result of the H0 hypotheses rejected. It is understandable that a problem-based learning model with a contextual approach has a significant influence on the competence of high school students. Based on the results of the research, it can be concluded that to enhance student competence, the teacher plays an important role in implementing problem-based learning as it can improve learning outcomes in various aspects, including cognitive, psychomotor, and affective. Then one of the recommended models is problem-based learning (PBL) with a context-based approach.